Kinetics and thermodynamics of Mn(II) removal from aqueous solutions onto Mg-Zn-Al LDH/montmorillonite nanocomposite - A.A. Bakr; N.A. Sayed; T.M. Salama; I.O. Ali; R.R. Abdel Gayed; N.A. Negm (Egyptian Journal of Petroleum)
This study deals with the removal of Mn(II) from aqueous solutions by Mg-Zn-Al LDH/montmorillonite nanocomposite. LDH adsorbent was prepared by co-precipitation method and the composite was prepared by physical mixing of LDH and MMT using high-shear action. The data revealed that the maximum adsorption efficiency were 24.5, 26.4 and 28.9 mg/g at adsorbent mass of 0.25 g/L, pH of 6.0, initial Mn(II) concentration of 80 mg/L, stirring rate of 160 rpm, contact time of 75 min and different temperatures of 298, 308 and 318 K, respectively. Langmuir and Freundlich models were used to optimize the adsorption process and pseudo-first order and pseudo-second order models were used to evaluate the adsorption kinetics of Mn(II) ions onto Mg-Zn-Al (LDH)/MMT nanocomposite. The data indicated that Langmuir model fits the experimental data better than Freundlich model and pseudo-second order model is sufficient to depict the kinetics of Mn(II) onto Mg-Zn-Al (LDH)/MMT composite. Also, the data obtained from thermodynamics study; Gibbs free energy (ΔG°), Enthalpy change (ΔH°), and Entropy change (ΔS°) revealed that the adsorption process is spontaneous, endothermic and randomness at the solid-solution interface during the process of adsorption. Keywords: Mn(II) removal, Kinetics and thermodynamics, Mg-Zn-Al LDH, Montmorillonite, Nanocomposite